IPO Underpricing Analysis: Underwriter Reputation as A Moderating Variable - Dwi Perkasa, Agustyan; Maiyaliza, Maiyaliza (Journal of Business and Management Review, 2024)
Research Aims: This study investigates the impact of company qualities and financial performance on underpricing (initial return) in firms undergoing initial public offerings from 2020 to 2023, with underwriter reputation moderating in this relationship. Design/methodology/approach: The study employed purposive sampling as the sampling strategy. The analysis technique used in this research is to use SEM (Structural Equation Modeling) analysis. Research Findings: The study's findings suggest that profitability and finance leverage have a detrimental impact on underpricing. Company Size and Company Age have no impact on Underpricing. Underwriter reputation can influence the impact of Return On Assets on Underpricing, but it does not affect the impact of Age, Size, and Equity Ratio of the Company on Underpricing. Firm size, age, return on assets, debt-to-equity ratio, and underwriter reputation are the variables that lead to underpricing. Theoretical Contribution/Originality: This study examines how underwriter reputation influences initial return and other parameters, including the debt-to-equity ratio, company age, organisation size, and return on assets. Prior studies used underwriter repute as an independent variable. This study's implications pertain to the initial market bidding activities of companies preparing to go public and other stakeholders interested in investigating factors affecting initial return. These stakeholders include potential investors considering the initial public offering, companies planning to go public, and researchers conducting further studies on this subject.